Sinus rhythm restoration and arrhythmia noninducibility are major predictors of arrhythmia-free outcome after ablation for long-standing persistent atrial fibrillation: a prospective study - Fiala, Martin; Bulková, Veronika; Škňouřil, Libor; Nevřalová, Renáta; Toman, Ondřej; Januška, Jaroslav; Špinar, Jindřich; Wichterle, Dan (Heart rhythm, 2015)
BACKGROUND: The impact of restoring sinus rhythm (SR) by initial ablation in patients with long-standing persistent atrial fibrillation (LSPAF) is not fully established. OBJECTIVE: The purpose of this study was to investigate the prognostic value of SR restoration at the initial procedure and arrhythmia noninducibility at the final repeat procedure for long-term outcome. METHODS: A total of 203 patients (22% female; age 59 ± 9 years) underwent stepwise catheter ablation for LSPAF. RESULTS: The procedural end-point of SR restoration was achieved in 50% of patients. During follow-up (median 48 months) and after 1.7 procedures per patient, 72% of patients were free from arrhythmia off antiarrhythmic drugs. Failure to restore SR was independently predicted by left atrial (LA) long-axis diameter ≥68 mm (relative risk [RR] 1.55, P = .03], proportion of high-voltage LA sites <20% (RR 1.62, P = .02), and left atrial appendage (LAA) atrial fibrillation cycle length (AFCL) <155 ms (RR 1.5, P = .05). Arrhythmia recurrence after the initial procedure was predicted by SR nonrestoration (RR 2.99, P <.000001) and LAA AFCL ≥155 ms (RR 1.90, P = .0002). Arrhythmia recurrence after the final procedure was predicted by SR nonrestoration at the initial procedure (RR 2.83, P = .0007), persistent AF duration ≥24 months (RR 2.74, P = .002), LAA outflow velocity <40 cm/s (RR 2.21, P = .006), and LAA AFCL ≥155 ms (RR 1.92, P = .02). In 115 patients with repeat procedure(s), failure to achieve arrhythmia noninducibility at the final procedure (19% of patients) was associated with arrhythmia recurrence (RR 8.9, P < .000001). CONCLUSION: SR restoration at the initial procedure and arrhythmia noninducibility at the last repeat procedure were major predictors of arrhythmia-free outcome after ablation for LSPAF.
Keywords: antiarytmika; čas; elektrofyziologické techniky kardiologické; reoperace; Prognosis; Noninducibility; Česká republika; výsledek terapie; katetrizační ablace; Sinus rhythm restoration; Risk Assessment; Middle Aged; registrace; mužské pohlaví; Long-standing persistent atrial fibrillation; Prospective Studies; recidiva; Czech Republic; Postoperative Complications; Registries; Reoperation; Atrial fibrillation; Electrophysiologic Techniques, Cardiac; Catheter Ablation; Time; Disease-Free Survival; ženské pohlaví; prognóza; hodnocení rizik; Humans; prospektivní studie; Recurrence; fibrilace síní; lidé středního věku; přežití bez známek nemoci; Anti-Arrhythmia Agents; Female; Atrial Fibrillation; Treatment Outcome; pooperační komplikace; lidé; Male; Outcome